PENGABDIAN KEPADA MASYARAKAT BAKTI SOSIAL BERSAMA PANTI ASUHAN AR-RIDHO, SIANTAN - Ainun Sa'adah; Meri Ropiqa; Puji Astuti; Zahro Mufidah (Jurnal Inovasi dan Terapan Pengabdian Masyarakat, 2021)
A community service program is a process of implementing the knowledge that has been learned in higher education to give many benefits to the community. One of the activities is in the form of social assistance. This activity aims to grow our awareness and social responsibility to give benefits to the community, especially in the orphanage environment. This community service program was held at Ar-Ridho Orphanage, Siantan. Some activities in the program are giving charity, motivation, and providing educational games for orphanage children. The community service program at Ar-Ridho Orphanage has finished smoothly, which is occurred by the active participation from all parties involved, Politeknik 'Aisyiyah Pontianak and the orphanage. This activity can strengthen the sense of brotherhood between educational institutions and social institutions.